Association between Pulmonary Embolism and Vitamin B12 Deficiency - Abdulkareem A. Jaragh; Naser Alhadhood (New Advances in Medicine and Medical Science Vol. 4, 2023)
We present a case of bilateral pulmonary embolism in a healthy female with vitamin B12 deficiency to further support the presence a causal relationship. The patient developed progressive dyspnea and fatigue of four days. She had tachycardia, tachypnea, and hypotension. CTPA showed bilateral PE. Her labs excluded other causes of thrombosis. On discharge, the patient was vitally stable and afebrile, and her hemoglobin was stable. She was given warfarin and follow up with hematology. We concluded that vitamin B12 deficiency causes elevation in homocysteine levels. This can affect the endothelium and platelets and result in increased risk of thromboses.